Preparation and characterization of In and Cu co-doped ZnS photocatalysts for hydrogen production under visible light irradiation - Melody, Kimi; Leny, Yuliati; Mustaffa, Shamsuddin (Elsevier, 2016)
In this work, a new photocatalyts In(0.1),Cu(x)-ZnS (x = 0.01, 0.03, 0.05) is successfully synthesized using simple hydrothermal method. The physical and chemical properties of the In and Cu co-doped ZnS photocatalyst were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), diffuse reflectance UV-visible spectroscopy (DR UV-visible) and photoluminescence spectroscopy (PL). The photocatalytic activity of the as-prepared In and Cu co-doped ZnS for hydrogen production from water with Na2SO3 and Na2S as sacrificial agent under visible light irradiation (λ ≥ 425 nm) was investigated. The presence of co-dopants facilitated the separation of electron-hole as well as increases the visible light absorption. The absorption edge of the co-doped ZnS photocatalyst shifted to longer wavelength as the amount of Cu increases. This indicates that the absorption properties depended on the amount of Cu doped. The photocatalytic activity of single doped In(0.1)-ZnS was significantly enhanced by co-doping with Cu under visible light irradiation. The highest photocatalytic activity was observed on In(0.1),Cu(0.03)-ZnS with the hydrogen production rate of 131.32 µmol/h under visible light irradiation. This is almost 8 times higher than single doped In(0.1)-ZnS.